THE DWELLERS’ ATTACHMENT TO JOGLO HOUSES IN KOTAGEDE - Deny Prastika Candra; Wara Indira Rukmi; Deni Agus Setyono (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2020)
The number of Joglo houses in existence has decreased in recent years. Any effort to conserve the remaining Joglo depends on the behavior of the dwellers in maintaining and utilizing Joglo properly. People who have stronger levels of place attachment tend to support conserving that place. Place attachment can be explained in three dimensions: the person, the place, and the psychological process. This study explores the attachment of the dwellers to their Joglo by using PLS-PM analysis to understand the relationships among these dimensions. The results show that the person and place dimensions have a positive effect on each of the aspects of the dimension of psychological process, but not all dimensions have a significant effect and the effect of each dimension varies. The evaluation of the model concludes that it has a high ability to explain the empirical conditions of the dweller’s place attachment to their Joglo